Semiconductor Bow‐Tie Nanoantenna from Coupled Colloidal Quantum Dot Molecules. Issue 26 (19th May 2021) - Cui, Jiabin; Koley, Somnath; Panfil, Yossef E.; Levi, Adar; Waiskopf, Nir; Remennik, Sergei; Oded, Meirav; Banin, Uri
Abstract: Top‐down fabricated nanoantenna architectures of both metallic and dielectric materials show powerful functionalities for Raman and fluorescence enhancement with relevance to single molecule sensing while inducing directionality of chromophore emission with implications for single photon sources. We synthesize the smallest bow‐tie nanoantenna by selective tip‐to‐tip fusion of two tetrahedral colloidal quantum dots (CQDs) forming a dimer. While the tetrahedral monomers emit non‐polarized light, the bow‐tie architecture manifests nanoantenna functionality of enhanced emission polarization along the bow‐tie axis, as predicted theoretically and revealed by single‐particle spectroscopy. Theory also predicts the formation of an electric‐field hotspot at the bow‐tie epicenter. This is utilized for selective light‐induced photocatalytic metal growth at that location, unlike growth on the free tips in dark conditions, thus demonstrating bow‐tie dimer functionality as a photochemical reaction center. Abstract : Selective tip‐to‐tip fusion of two tetrahedral nanocrystal quantum dots yielded the smallest bow‐tie nanoantenna architecture, which manifests an electromagnetic‐photocatalytic hotspot at its epicenter.